A Review of Antenna Design for UHF RFID Tags (International Journal of Food and Nutritional Sciences, 2022)
RFID stands for Radio Frequency Identification and refers to a wireless technology that consists of two parts: tags and readers. The reader is a device that emits radio waves and receives signals from the RFID tag through one or more antennas. Tags may be passive or active, communicating their identification and other information to nearby readers through radio waves. Passive RFID tags do not have a battery and are powered by the reader. The purpose of this article is to provide an overview of antenna design for passive radio frequency identification (RFID) tags. We go through the different criteria for such designs, describe a general design approach that includes range measuring tools, and focus on one real-world application: RFID tags for warehouse box monitoring. For this application, a loaded meander antenna design is presented, with different practical issues such as sensitivity to manufacturing process and box content examined. The findings of modeling and simulation are also given, and they are in excellent agreement with the measurement data.